BODIPY Containing PMMA-Based Electrospun Nanofibers as Dielectric Materials - Gunduz, Ezel Ozturk; Aksoy, Burcu Topaloglu; Gurbuz, Hande Eserci; Tataroglu, Adem; Dere, Aysegul; Yakuphanoğlu, Fahrettin; Gevrek, Tugce Nihal (Wiley-V C H Verlag Gmbh, 2025)
The ease of modification of boron dipyrromethene (BODIPY) enables the preparation of diverse structures with versatile optoelectronic properties. In this study, the synthesis and characterization of a new BODIPY derivative (4) bearing a methacrylate moiety at the meso position are reported. The BODIPY monomer (4) is polymerized with methyl methacrylate (MMA) as a comonomer and characterized via H-1 NMR and size exclusion chromatography (SEC). The resulting polymers, P[MMA-r-BODIPYMA] and PMMA are separately processed into nanofibers through electrospinning, and their morphologies are analyzed using a scanning electron microscope (SEM). Impedance analysis reveals that the impedance (Z) of the nanofibers decreases with increasing frequency up to approximate to 1 kHz, and remains constant beyond this point. The dielectric constant (epsilon ') and dielectric loss (epsilon '') decrease, while AC conductivity (sigma ac) increases with frequency. The impedance behavior of the nanofibers shows a linear relationship with frequency, indicating polarization under an alternating current electric field. Incorporating BODIPY into nanofibers reduces the dielectric constant due to alterations in dielectric polarization. These frequency-dependent impedance and dielectric properties suggest that the synthesized nanofibers have promising applications in nanotechnology-based electronic devices.
Keywords: BODIPY; dielectric properties; nanofibers; P[MMA-r-BODIPYMA]; PMMA